Association of RASGRP1 with type 1 diabetes is revealed by combined follow-up of two genome-wide studies. Issue 8 (21st May 2009) - Qu, H Q; Grant, S F A; Bradfield, J P; Kim, C; Frackelton, E; Hakonarson, H; Polychronakos, C
Abstract : Background: The two genome-wide association studies published by us and by the Wellcome Trust Case–Control Consortium (WTCCC) revealed a number of novel loci, but neither had the statistical power to elucidate all of the genetic components of type 1 diabetes risk, a task for which larger effective sample sizes are needed. Methods: We analysed data from two sources: (1) The previously published second stage of our study, with a total sample size of the two stages consisting of 1046 Canadian case–parent trios and 538 multiplex families with 929 affected offspring from the Type 1 Diabetes Genetics Consortium (T1DGC); (2) the Rapid Response 2 (RR2) project of the T1DGC, which genotyped 4417 individuals from 1062 non-overlapping families, including 2059 affected individuals (mostly sibling pairs) for the 1536 markers with the highest statistical significance for type 1 diabetes in the WTCCC results. Results: One locus, mapping to a linkage disequilibrium (LD) block at chr15q14, reached statistical significance by combining results from two markers (rs17574546 and rs7171171) in perfect LD with each other (r2  = 1). We obtained a joint p value of 1.3×10 −6, which exceeds by an order of magnitude the conservative threshold of 3.26×10 −5 obtained by correcting for the 1536 single nucleotide polymorphisms (SNPs) tested in our study. Meta-analysis with the original WTCCC genome-wide data produced a p value of 5.83×10 −9 . Conclusions: A novel type 1 diabetes locus was discovered. It involves RASGRP1, a gene known to play a crucial role in thymocyte differentiation and T cell receptor (TCR) signalling by activating the Ras signalling pathway.